Human rights protection by Non-Governmental Organisations (NGOs) for stateless Rohingya in Malaysia / Mohd Ramlan Mohd Arshad, Mohd Na’eim Ajis and Rozita Abdul Mutalib - Mohd Arshad, Mohd Ramlan; Ajis, Mohd Na’eim; Abdul Mutalib, Rozita (2022)
The term ‘refugee’ refers to an individual who has been forced to leave his or her homeland to escape persecution, war, or natural disasters. A refugee has a well-founded fear of persecution, which may be directed towards a specific social group for reasons of religion, race, nationality, political opinion, or membership. This study was conducted to examine the protection of the human rights of Rohingya refugees during their stay in Malaysia. In total, 300 Malaysians were involved in answering an online questionnaire that utilized a Likert scale measurement. The data collected was formulated using the Statistical Package for the Social Science (SPSS). Overall, following the profiling of the human rights of refugees in Malaysia, the findings indicated that the most significant right of the refugees was the Right to Employment. Refugees should be able to obtain employment rights as Malaysia faces a shortage of workers, especially in certain fields offering ‘3D jobs’. This refers to industries that are dirty, difficult, and dangerous.